HUBUNGAN TINGKAT KECEMASAN DENGAN KUALITAS TIDUR PADA LANSIA PENDERITA HIPERTENSI - Puspita, Tantri; Ramadan, Hasim; Budhiaji, Purbayanty; Sulhan, M. Hadi (Universitas 'Aisyiyah Bandung, 2019)
Sleep quality of elderly is influenced by psychological conditions. Elderly with hypertension are affected not only by physical but also pshychological conditions. Anxiety is a part of its. This study was used a cross-sectional approach to identify the relationship between anxiety level (independent variable) and sleep quality in the elderly (dependent variable) with hypertension in the working area of ​​Karangmulya Health Center, Garut Regency. This study was used Zung Self-rating Anxiety Scale (ZSAS) and the Pitsburgh Sleep Quality Index (PSQI) questionnaires. The results showed that the majority of respondents were female, 63 respondents (65.6%) and widow/widower (69.8%). The Correlation analysis between the level of anxiety and sleep quality of elderly patients with hypertension showed results P-value = 0.041(p<0.05), which means there was a relationship between the level of anxiety and sleep quality in elderly patients. It is expected that health care workers especially nurses can help the elderly to improve sleep quality through handling anxiety in elderly people with hypertension.